Immediate Effect of Whole-Body Vibration Exercise Performed in Vertical Versus Side-Alternating Displacement Modes on Physiological Parameters, Perception of Effort, Strength and Functionality in Adults with Obesity - Reis-Silva, Aline; Cardoso, André Luiz Bandeira Dionizio; Coelho-Oliveira, Ana Carolina; Batouli-Santos, Daniel; Santos, Gabriel Siriano Damasceno dos; Mazini, Jennyfer Silva; Valério-Penha, Ana Gabriellie; Andrade-Nascimento, Alessandra; Moura-Fernandes, Marcia Cristina; Taiar, Redha; Sartorio, Alessandro; Sá-Caputo, Danúbia da Cunha de; et al. (Diagnostics, 2026)
Background: Obesity, defined as an abnormal accumulation of body fat, is becoming a global epidemic. Individuals with obesity may present with increas...
Keywords: obesity; physical functional performance; vibration; vital signs